High-dielectric TiO2-mediated g-C3N4 enhanced self-polarized PVDF hybridized film for highly sensitive wearable triboelectric pressure sensors - Chiu, Yen-Shuo; Rinawati, Mia; Chang, Ling-Yu; Aulia, Sofiannisa; Shi, Ping-Chen; Haw, Shu-Chih; Huang, Wei-Hsiang; Wulan Septiani, Ni Luh; Yuliarto, Brian; Yeh, Min-Hsin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
[Display omitted] •A triboelectric pressure sensor was constructed based on high-dielectric TiO2-mediated g-C3N4 modified PVDF.•The dielectric constant of g-C3N4 can be enhanced by integrating TiO2, resulting in a more negative PVDF.•TiO2 effectively prevents the g-C3N4 aggregation, resulting in maximizing the effective self-polarization.•PVDF/TiO2-CN triboelectric pressure sensor exhibits 3-fold increase compared to pristine PVDF one. Triboelectric nanogenerators (TENGs) have emerged as a promising technology, enabling triboelectric pressure sensors (TES) to achieve high sensitivity and self-powered functionality. A key factor in enhancing their performance is selecting triboelectric materials that can effectively utilise electrostatic induction and triboelectrification. Among them, PVDF has drawn interest due to its excellent flexibility and strong tribo-negative characteristics. Nevertheless, the intrinsic multiphase structure of pristine PVDF limits its overall triboelectric performance. To overcome this bottleneck, in this work, we address these limitations by engineering a PVDF-based composite film incorporating a series of TiO2-modified g-C3N4 (TiO2-CN). Introducing TiO2 nanoparticles into the g-C3N4 structure effectively enhances its inherently low dielectric constant, forming an integrative heterostructure with a uniform and interconnected composite network. Fine-tuning the TiO2 composition within this heterostructure effectively prevents the g-C3N4 particle aggregation, resulting in a homogeneous composite matrix and maximizing the effective self-polarization. PVDF/TiO2-CN-based TENG significantly increased triboelectric output, generating 75 V more than the pristine PVDF, sufficient to power 94 LEDs in series. Furthermore, the PVDF/TiO2-CN-based TES demonstrated a remarkable sensitivity of 1.79 V·kPa−1, a threefold improvement over pristine PVDF’s 0.51 V·kPa−1 sensitivity. These findings highlight the transformative potential of PVDF/TiO2-CN composites in advancing next-generation self-powered wearable pressure sensors.